Penerapan Prinsip Indemnitas Pada Asuransi Kendaraan Bermotor - Selvi Harvia Santri (UIR Law Review, 2019)
The loss suffered by the insured can be processed by submitting a claim to the insurance company, so that compensation can be paid. The compensation referred to in insurance must apply the principle of Indemnity. This principle applies the principle of equilibrium, where compensation imposed by the insured may not exceed the price or the sum insured submitted prior to the loss. This principle only applies to loss insurance, not to insurance amount of money (Life insurance). The problem discussed is how to regulate the principle of Indemnity on Motor Vehicle Insurance and how to apply the principle of Indemnity to Motor Vehicle Insurance. The purpose of this paper is to determine the regulation and application of the principle of Indemnity on Motor Vehicle Insurance. The Legal Research Method used is an Empirical Jurisdiction by observing Insurance companies then analyzing the results according to existing insurance law regulations. Results and Discussion The regulation of the Indemnity Principle on Motorized Vehicle Insurance is only discussed in the Commercial Law Act, namely article 246 KUHD, Article 353 KUHD, while Law No. 40 of 2014 concerning Insurance Business Has not discussed in detail the Indemnity arrangement, so new provisions specifically discussing the Principle of Indemnity. The application of the Indemnity Principle to Motor Vehicle Insurance is set forth in the Indonesian Motor Vehicle Standard Policy. In practice the principle of indemnity has not been carried out according to the policy, so that it can cause obstacles in compensation.